Species adulteration in raw milk samples using polymerase chain reaction-restriction fragment length polymorphism - Ewida, Rania M.; El-Magiud, Doaa Safwat M. Abd (Veterinary World, 2018)
Milk adulteration is pivotal because it leads to worse effects in public health as human adverse reactions with clinical signs ranged from gastrointestinal signs to anaphylactic shock. This study was carried out to estimate the prevalence of adulteration in buffalo's milk sold in Assiut City, Egypt. A total of 50 raw buffalo's milk samples were collected and examined for adulteration by addition of cow's milk. The examination carried out by applying polymerase chain reaction-restriction fragment length polymorphism technique using gene primers and Hinf I enzymes. The size of target gene was 360 bp in both animal species and amplicon can be digested using Hinf I enzyme, this restriction enzyme divided the essential band to clear three bands at 360, 210, and 150 bp in cows' milk, while, the enzyme could not be cleaved the amplicon in buffalo's samples. The obtained results cleared that the incidence of adulteration of buffalo's milk very high percentage reaches 90%. It could be concluded that the raw buffalo's milk sold in Assiut City subject to fraudulent practice and thus can lead to public health hazards.